A Comparative Study Of The Printed And Hypertext Novel 10:01 - Ladan, Modir (2015)
In the postmodern era. the mutual impression between printed literature and digital media has embedded narratives into interactive environments and new genres like hypertext fiction are created. Lance Olsen has adapted his postmodern printed novel entitled 10:01 into the hypertext version which is in the digital fonn. Considering that both novels are postmodern literary works by the same author this adaptation has produced certain questions; how can the narrative structure of the hypertext fiction be compared to the printed one? The second question that arises is how can aesthetic experiences be different in the reading processes of both versions?